Dietary Intake of Structured Lipids with Different Contents of Medium‐Chain Fatty Acids on Obesity Prevention in C57BL/6J Mice. Issue 8 (20th June 2017) - Zhou, Shengmin; Wang, Yueqiang; Jiang, Yuanrong; Zhang, Zhongfei; Sun, Xiangjun; Yu, Liangli (Lucy)
Abstract: Three medium‐ and long‐chain triacylglycerols (MLCT) with different contents of medium‐chain fatty acids (MCFA) (10% to 30%, w/w) were prepared and evaluated for their anti‐obesity potential in C57BL/6J mice. The group fed with a high fat diet of MLCT containing 30% (w/w) MCFA showed significantly decreased body weight and fat mass ( P < 0.05) relative to the control mice fed an obesity‐inducing high fat rapeseed oil diet. In addition, serum parameters including triacylglycerols, total cholesterol, glucose, high‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol, apolipoprotein A1 and apolipoprotein B in the treatment group fed with 30% (w/w) MCFA were close to those of mice fed with a low fat rapeseed oil diet, but significantly different ( P < 0.05) from those of the obesity control group. Moreover, the intake of MLCT with high content of MCFA reduced the size of adipocytes. In addition, the visceral fat and liver weights, as well as the liver triacylglycerol for 3 treatment groups were lower than those of the obesity control group. These results demonstrate the great potential of MLCT with high content of MCFA in weight loss.